Using participatory action research to develop antenatal education in preparation for motherhood - Brady, Vivienne (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2012)
The current growth in the use of maternity services in Ireland is reflected by a 5% increase noted in births nationally between 2007 and 2008, with 75,587 births notified to the National Perinatal Reporting System (NPRS) in 2008 (Economic and Social Research Institute 2010). How services are provided in response to this demand is an indication of how women are situated and positioned in Irish society (Kennedy 2004). Antenatal education (ANE) is offered by every maternity unit in the Republic of Ireland on the premise that it prepares women for birth and motherhood. Notwithstanding this, there is evidence to suggest that conventional models of hospital-based antenatal education fail to meet women’s social and psychosocial needs (Barclay et al. 1997, Kennedy 2002, Matthey et al. 2002, Schott 2003) in preparation for motherhood (Nelson 2003, Nolan and Foster 2005). Critiques of traditional methods of ANE suggest that class facilitators have normalised and fostered acceptance of an increasingly medicalised, technological model of childbirth through the medium of antenatal education (Oakley 1980, Fleming 1992, Kitzinger 2005), at a time during pregnancy, when women anticipate change and are open to outside influences (Chalmers 1997). Minimal consultation with women in planning and developing services is a feature of maternity care in Ireland and is absent most certainly at strategic policy levels (O’Connor 2006, Devane et al. 2007).
Keywords: Nursing & Midwifery, Ph.D.; Ph.D. Trinity College Dublin